Measurement of the free neutron lifetime using the neutron spectrometer on NASA's Lunar Prospector mission - Wilson, Jack T.; Lawrence, David J.; Peplowski, Patrick N.; Eke, Vincent R.; Kegerreis, Jacob A. (Physical Review C, 2021)
We use data from the Lunar Prospector Neutron Spectrometer to make the second space-based measurement of the free neutron lifetime finding τ n = 887 ± 14 stat + 7 − 3 syst s, which is within 1 σ of the accepted value. This measurement expands the range of planetary bodies where the neutron lifetime has been quantified from space, and by extending the modeling to account for nonuniform elemental composition, we mitigated a significant source of systematic uncertainty on the previous space-based lifetime measurement. This modeling moves space-based neutron lifetime measurement towards the ultimate goal of reducing the magnitude of the systematics on a future space-measurement to the level of those seen in laboratory-based experiments.
EPrint Processing Status: Full text deposited in DRO